(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: What is the species composition of fungi on the territory of the Nyzhniovorsklianskyi Regional Landscape Park? Location: Poltava Region, Ukraine. Materials and methods: authors’ own mycological collections, published data, and traditional identification. Nomenclature: https://www.indexfungorum.org, Hyde et al. 2024, Mosyakin & Fedoronchuk 1999. Results: As a result of mycological survey of the territory of the Regional Landscape Park "Nyzhniovorskliansky" (Poltava region, Ukraine) and analysis of literature data, 304 species from 129 genera of fungi belonging to Oomycota, Ascomycota and Basidiomycota were recorded. Of these, eight species were previously reported by the authors for the first time for Ukraine. They are Agrocybe splendida, Deconica inquilina, Inosperma cervicolor, Mallocybe agardhii, Panaeolus ater, Peronospora chelidonii, Pluteus robertii and Psathyrella cotonea. Besides them, Agaricus abruptibulbus, A. altipes, A. bernardii, A. cupreobrunneus, A. rusiophyllus, Amanita regalis, Bolbitius vitellinus, Cercopemyces rickenii, Entoloma aprile, E. vernum, Inocybe nitidiuscula, Laccaria tortilis, Lactarius helvus, Lepiota felina, Pluteus atromarginatus, P. petasatus, Russula gracilis, R. mollis and Tricholoma maluvium are new for the Left Bank Forest-Steppe. Other eight species, Agaricus bernardi, A. cupreobrunneus, Calvatia gigantea, Gyroporus castaneus, Leccinum holopus, Macrolepiota mastoidea, Montagnea radiosa and Saproamanita vittadinii, are included in the Red List of Poltava region. Three species, Agaricus bresadolanus, Cercopemyces rickenii and Montagnea radiosa, are listed in the Red Data Book of Ukraine. Conclusions: The compiled list of fungi is not exhaustive, but it reflects the taxonomic structure of the species composition of macromycetes in the studied park quite well. Undoubtedly, a significant number of new and interesting fungi finds can be expected on the territory of the Nyzhniovorsklianskyi Regional Landscape Park, so mycological research should be continued here.